Ten Lectures on Diachronic Construction Grammar - Hilpert, Martin (Distinguished Lectures in Cognitive Linguistics, 2021)
In this book, Martin Hilpert lays out how Construction Grammar can be applied to the study of language change. In a series of ten lectures on Diachronic Construction Grammar, the book presents the theoretical foundations, open questions, and methodological approaches that inform the constructional analysis of diachronic processes in language. The lectures address issues such as constructional networks, competition between constructions, shifts in collocational preferences, and differentiation and attraction in constructional change. The book features analyses that utilize modern corpus-linguistic methodologies and that draw on current theoretical discussions in usage-based linguistics. It is relevant for researchers and students in cognitive linguistics, corpus linguistics, and historical linguistics.. Readership: The book is especially relevant for researchers and students in cognitive linguistics, corpus linguistics, and historical linguistics.